Overcoming Electricity Crisis in Pakistan An Overview of the Renewable Energy Status and Development in Pakistan - Rehman, Syed Aziz Ur; Cai, Yanpeng; Nafees, Mohammad; Walasai, Gordhan Das; Mirjat, Nayyar Hussain; Rashid, Wajid (Journal of Environmental Accounting and Management, 2026)
Pakistan is currently facing energy crisis in the form of electricity and natural gas load shedding due to the insufficient availability of indigenous fossil fuels. On the other hand, the country possesses huge renewable energy resources (RERs) which are merely harnessed due to lack of institutional and governmental support. This paper is designed to discuss the past and current energy demand and supply situation in the country followed by an assessment of the potential for RERs which can be harnessed for meeting energy demand of the country. An extensive literature review is undertaken in this study, focusing therein the potential of RERs in the country covering hydel, solar, wind, biomass and geothermal energy resources. It is revealed from this review that the highest potential out of all RERs exist for solar energy, i.e. 2900 GW followed by wind energy 346 GW, hydropower 100 GW and biomass energy 12.74 GW. Besides, it is observed that the highest number of ongoing potential energy projects pertain to mega hydropower generation. The research concludes that Pakistan needs to invest more and more in hydel energy and keep the pace of research and investment in the solar and wind energy as much as possible so that country indigenously self-sufficient and economically viable for all types of RERs in the long run.